Environmental stress cracking (ESC) resistance of polycarbonate/SiO2 nanocomposites in different media. Issue 43 (7th July 2017) - Nomai, Jiraporn; Schlarb, Alois K.
ABSTRACT: Polycarbonate (PC) nanocomposites containing different nano‐SiO2 contents were prepared using a twin‐screw extruder followed by injection molding. The mechanical behavior and environmental stress cracking (ESC) resistance of the nanocomposites were investigated. Compared to neat PC, the incorporation of nanofiller leads to a slight improvement in Young's modulus, tensile strength, and notched impact strength properties. Interestingly, the nanofiller enhanced the environmental stress cracking resistance of PC in different fluids (isopropanol, methanol, aqueous urea solution, and deionized water) vastly. The correlation of the mode I critical stress intensity factor with the Hansen solubility parameter shows a very good agreement for different fluids and thus allows the prediction of the stress cracking behavior as a function of the filler content for different stress‐cracking agents. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45451. Abstract :